(untitled) (Canadian Journal of Native Studies, 2026)
Examining how acculturative changes affect Inuit culture—especially lifestyle, customs, Inuktut language proficiency, and intellectual endeavours—I assess Inuit culture and identity within the fabric of multicultural Canada. Taking John W. Berry’s Fourfold Model of acculturation as an investigative framework, I use Peter Weinreich’s Identity Structure Analysis to study the effects of acculturation on Inuit living in both Arctic Canada and the South. I propose that access to Southern culture for a people with strong attachment to the land transforms personal and collective identity and creates amalgamated identities—especially for Inuit relocated to urban settings— which reflect both tradition and acculturative build-up. The official recognition of the Inuit Nunangat, the homeland, was a fundamental necessity for positive self-image and is a driving force today in asserting a uniquely Inuit identity within the cultural context of Canada. Building on Inuit-led amendments to the curriculum already in place across the North, I propose a heritage language-based and traditional knowledge-enhanced school curriculum implementing the teaching of traditional texts, such as myths, classic tales, and songs in Inuktut in order to foster traditional knowledge—known as IQ, or Inuit Quaujimajatuqangit— and Inuktut fluency, which are vital aspects of cultural retainment for Inuit in Canada.